D-Dimer Assays in Diagnosis and Management of Thrombotic and Bleeding Disorders - Bates, Shannon M. (Seminars in Thrombosis and Hemostasis, 2012)
D-dimer is a global indicator of coagulation activation and fibrinolysis and, therefore, an indirect marker of thrombotic activity. The utility of D-dimer measurement has been evaluated in several clinical situations including the exclusion of venous thromboembolism (VTE), prediction of future risk of VTE, and the diagnosis and monitoring of disseminated intravascular coagulation (DIC). Assay standardization remains problematic and clinicians need to be aware of variability in D-dimer assay performance and the characteristics of their institution's test when making clinical decisions. This article will review the available evidence for the utilization of D-dimer antigen measurement in the management of thrombotic and bleeding disorders.
Keywords: D-dimer; venous thromboembolism; recurrence; anticoagulant duration